Associations of lifestyle factors with amyloid pathology in persons without dementia - Oomens, Julie E.; Vos, Stephanie J. B.; Maserejian, Nancy N.; Boada, Mercè; Didic, Mira; Engelborghs, Sebastiaan; Fladby, Tormod; van der Flier, Wiesje M.; Frisoni, Giovanni B.; Frölich, Lutz; Gill, Kiran Dip; Grimmer, Timo; et al. (Journal of Alzheimer's disease, 2025)
Background - The association between lifestyle factors and Alzheimer's disease (AD) pathophysiology remains incompletely understood. - Objective - The aim of this study was to assess the association of alcohol consumption, smoking behavior, sleep quality and physical, cognitive, and social activity with cerebral amyloid pathology. - Methods - For this cross-sectional study, we selected participants from the Amyloid Biomarker Study data pooling initiative. We used generalized estimating equations to assess associations of dichotomized lifestyle measures with amyloid pathology. - Results - We included 9171 participants with normal cognition (NC) and 2555 participants with mild cognitive impairment (MCI) from the Amyloid Biomarker Study. Of participants with NC, 58% were women, 34% were APOE ε4 carrier, and 27% had amyloid pathology. Of participants with MCI, 48% were women, 47% were APOE ε4 carrier, and 57% had amyloid pathology. In NC, cognitively active participants were less likely to have amyloid pathology (OR = 0.77, 95%CI 0.66-0.89, p < 0.001). In MCI, participants who had ever smoked or had sleep problems were less likely to have amyloid pathology (OR = 0.85, 95%CI 0.73-0.99, p = 0.029; OR = 0.62, 95%CI 0.45-0.86, p = 0.004). - Conclusions - In NC, cognitive activity was associated with a lower frequency of amyloid pathology. In MCI, favorable lifestyle behaviors were not associated with a lower frequency of amyloid pathology. The results of the current study contribute to the broader evidence base on lifestyle and AD by further characterizing the role of lifestyle behaviors in AD pathology across different clinical stages.
Online verölffentlicht: 13. November 2025
Gesehen am 09.02.2026